Kompetensi Profesional Guru Dalam Mengembangkan Curiosity Dan Kreatifitas Siswa Madrasah Ibtidaiyah Kota Salatiga - Paramita Ayu Ekasari; Taufiqur Rohman (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to develop students' curiosity and creativity through the professional competences of teachers. This research is motivated by the number of educators who want to re-emphasize the presence of character education. In addition, the low level of curiosity and creativity of students to learn new things results in the knowledge obtained by students is not optimal.This study used a naturalistic qualitative method with cluster random sampling technique. As for the subjects of this study, students and teachers at MI Ma'arif Mangunsari and MI Ma'arif Kumpulrejo 02 Salatiga. The results showed that teachers who have been certified have understood the concept of professional competence by carrying out the obligations that are their responsibility. The teacher provides additional quality of learning that has an impact on the development of curiosity of students through their professional competences. Teachers who are able to provide additional quality of learning that have an impact on the development of student creativity. The character development of students must continue to be carried out to create a superior generation not only in academics but also in character.